The health and welfare of fed cattle after transport to commercial slaughter facilities - Lee, Tiffany (Kansas State University, 2017)
Cattle health and welfare are of utmost concern to producers, packers, processors, and consumers of beef. In addition, poor animal welfare can lead to decreases in economic return, in the form of production losses, product losses, or even live animal losses. Two major contributors to such losses include carcass bruising and cattle fatigue, or Fatigued Cattle Syndrome. Bruising in fed beef cattle costs the industry millions of dollars annually, and cattle fatigue leads to production losses and animal death during and after transport. Much research in cattle welfare is focused upon the more vulnerable classes of cattle in the industry, such as small calves, cull beef cows, and cull dairy cows. Limited research exists on the animal welfare concerns in fed beef cattle, likely because these animals are considered healthier and better fit for transport compared to other classes. The overall goal of this research was to assess the health and welfare of fed cattle after transport to commercial slaughter facilities by addressing two large concerns in the industry: 1) bruising in fed cattle and 2) Fatigued Cattle Syndrome and its prevalence and physiologic characteristics. The first objective of this research focused upon bruising, and was to determine whether a relationship exists between trauma incurred during unloading and prevalence of carcass bruising in finished beef cattle at commercial slaughter facilities. In addition, other risk factors which may contribute to carcass bruising in finished beef cattle are addressed. The second and third objectives focused upon Fatigued Cattle Syndrome in the fed cattle population. The second objective of this research was to determine the prevalence of abnormal mobility scores and the clinical signs associated with to abnormal mobility in finished cattle in six commercial slaughter facilities across the United States. The third objective was to determine if mobility score and clinical signs reflect concurrent changes in physiologic parameters such as blood concentrations of specific biochemical markers and biomechanical integrity of hooves. This information is both valuable and novel in the fed beef cattle industry. Along with the implementation of practices that will promote better health and welfare of fed cattle presented to slaughter facilities, gathering such information will help improve animal welfare, increase economic returns, and strengthen consumer confidence in the industry.
Keywords: Cattle; Welfare; Beef; Bruising; Fatigue